2017
DOI: 10.9790/487x-1901051319
|View full text |Cite
|
Sign up to set email alerts
|

Transdisciplinary Research in Higher Education: Towards a Paradigm for Sustainable Development

Abstract: This review provides an understanding of and justification for the transdisciplinary research(TDR)as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
(18 reference statements)
0
1
1
Order By: Relevance
“…Previous research has shown that there can be significant communication challenges among different disciplines in transdisciplinary research both inside (Harris and Lyon, 2013;Stablein et al, 2022) and outside of FEWS (Rudhumbu et al, 2017). Although we recognized some communication challenges upon reflecting on the collaboration, actual coded segments of meeting notes did not show evidence of this communication challenge.…”
Section: Communicationcontrasting
confidence: 61%
“…Previous research has shown that there can be significant communication challenges among different disciplines in transdisciplinary research both inside (Harris and Lyon, 2013;Stablein et al, 2022) and outside of FEWS (Rudhumbu et al, 2017). Although we recognized some communication challenges upon reflecting on the collaboration, actual coded segments of meeting notes did not show evidence of this communication challenge.…”
Section: Communicationcontrasting
confidence: 61%
“…However, in line with recent evaluations of TDR in higher education (e.g. Rudhumbu et al , 2017; Appel and Kim-Appel, 2018; Fam et al , 2019; Guimarães et al , 2019; Duncan, 2012; National Research Council, 2013), we felt that our approach to reflective, processual and solutions-oriented TDR sometimes sat awkwardly with the lived realities of an academic setting that is increasingly fuelled by corporate objectives (Donoghue, 2008) and resource pressures, particularly under pandemic conditions. Our complex, conceptually-developmental project, we perceived, was unlikely to progress quickly through university processes and would need greater time for formulation than most research ventures.…”
Section: Resultsmentioning
confidence: 55%